Atividade antimicrobiana de enxaguatórios bucais sem álcool à base de clorexidina sobre candida albicans - Maekawa, Lilian Eiko; Brighenti, Fernanda Lourenção [UNESP]; Lamping, Roberta [UNESP]; Oliveira, Luciane Dias de [UNESP]; Marcacci, Sidney; Koga-Ito, Cristiane Yumi (My University, 2010)
The aim of this study was to evaluate the antimicrobial activity of alcohol-free mouthwashes on Candida albicans. Twenty clinical isolates of C. albicans and one reference strain (ATCC 18804) were evaluated after exposure to two 0.12% chlorhexidine-based and alcohol-free (“Ca” and “Or”) in comparison to gluconate chlorhexidine with ethanol (positive control). The maximum inhibitory dilution (MID) and maximum fugal dilution (MFD) were determined by the microdilution method. Twelve serial dilutions (from 50 to 0.02%) were prepared in duplicate. Then, 100 µL of C. albicans suspension (106 cells.mL–1) were added to the wells. After incubation (37 °C/24 hours), MID was determined by reading the optical density. For MFD determination, the content of the wells were plated on Saouraud agar. For MID, there were no differences between groups Or and control, but Ca group showed a MID statistically higher (Kruskal-Wallis, p = 0.0012). For MFD, there were no differences between Ca and control (Mann-Whitney test, p = 0.1631). It can be concluded that Ca group showed a fungicid activity against C. albicans similar to the control, but lower fungistatic activity when compared to the control. Group Or showed only a fungistatic action similar to control.

A proposta deste estudo foi avaliar a atividade antimicrobiana de enxaguatórios bucais, à base de clorexidina, sem álcool na sua composição, sobre Candida albicans. Foram avaliados vinte isolados clínicos de C. albicans e uma cepa de referência (ATCC 18804) frente a dois enxaguatórios à base de digluconato de clorexidina 0,12% e sem etanol (“Ca” e “Or”), em comparação ao enxaguatório de gluconato de clorexidina com etanol (controle positivo). A máxima diluição inibitória (MDI) e a máxima diluição fungicida (MDF) foram determinadas pelo método de microdiluição. Foram realizadas 12 diluições seriadas dos produtos (de 50 a 0,02%) em duplicata. Em seguida, foram acrescentados 100 µL da suspensão de C. albicans (106 células.mL–1) nos poços das placas. Após incubação (37 °C/24 horas), a MDI foi determinada por meio da leitura das densidades ópticas. Para determinar a MDF, foram realizadas semeaduras do conteúdo dos poços em ágar Sabouraud. Não houve diferenças estatísticas entre os grupos Or e controle para a MDI, mas o grupo Ca mostrou uma MDI estatisticamente maior (Kruskal-Wallis, p = 0,0012). Já para MDF, não houve diferenças estatísticas entre os grupos Ca e controle (Teste de Mann-Whitney, p = 0,1631). Pode-se concluir que o grupo Ca apresentou atividade fungicida sobre C. albicans semelhante ao controle, mas menor ação fungistática em comparação ao controle, enquanto que o Or apresentou apenas ação fungistática semelhante ao controle sobre os isolados avaliados.
Antimicrobial activity of alcohol-free chlorhexidine mouthwashes on candida albicans
Keywords: Antifungal agents; Mouthwashes; Candida albicans; Chlorhexidine; Antimicóticos; Antissépticos bucais; Candida albicans; Clorexidina.